Mica nanosheet as well as preparation method and application thereof

By inserting ionic liquid into the mica sheet layer and using ultrasonic processing technology, the problems of small size and many lattice defects in the prior art are solved, and the preparation and large-size and high-quality mica nanosheets are achieved. , suitable for a variety of high-performance applications.

CN119390081APending Publication Date: 2025-02-07NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411351198.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

It is difficult to prepare large-size, high-quality mica nanosheets in the prior art, and lattice defects caused by ball milling and peeling methods limit their use in high-performance applications.

Method used

Ion liquid is used as a small molecule intercalator, and the ionic liquid is inserted between the mica sheets by stirring and mixing. The mica nanosheets are stripped with ultrasonic technology, which avoids the "impact crushing effect" during the ball milling process, thereby reducing lattice defects. .

Benefits of technology

The high yield and large-size mica nanosheets are achieved. The product has a large size, a sheet diameter of 1-5 μm, a thickness of 0.5-5 nm, and a surface loaded with ionic liquid, high quality and few defects, suitable for thermal conductivity Applications such as sheets, thermally conductive composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390081A_ABST
    Figure CN119390081A_ABST
Patent Text Reader

Abstract

The invention provides a mica nanosheet as well as a preparation method and application thereof, and relates to the technical field of nano material preparation. According to the preparation method of the mica nanosheet, the mica, the ionic liquid and the solvent are mixed and then subjected to ultrasonic treatment, and the large-size ultrathin mica nanosheet is obtained. According to the method, the ionic liquid is used as an intercalation agent and is intercalated between mica sheet layers, so that the distance between the mica sheet layers is enlarged, the interaction force between the mica sheet layers is weakened, the mica nanosheet subjected to ultrasonic treatment is easier to strip, lattice defects are not prone to being generated in the stripping process of the mica nanosheet, and the service life of the mica nanosheet is prolonged. The prepared mica nanosheet is high in quality, few in defect, low in impurity content and good in dispersity, can be used as a barrier functional filler of a heat-conducting sheet, a heat-conducting composite material, polyester or an anticorrosive coating, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a mica nano sheet and a preparation method and application thereof. Background Art

[0002] As a typical two-dimensional material, natural mica has the advantages of high barrier, high strength, large specific surface area, excellent toughness, thermal / chemical stability, high temperature insulation and electrical insulation, so it has received widespread attention in the fields of metal corrosion protection and biopharmaceuticals. However, the strong intermolecular forces and ionic bonds between natural mica layers make it extremely difficult to exfoliate and prepare large-sized and high-quality mica nanosheets, which has become a key problem restricting the commercial application of mica nanosheets.

[0003] Mechanical exfoliation techniques such as ball milling, ultrasonic method, high-speed stirring method, water jet method and air flow crushing method are often used to prepare mica nanosheets. Among them, the ball milling exfoliation method has significant comparative advantages in large-scale preparation and cost, and has always been the mainstream exfoliation technology. The ball milling exfoliation method is to fill the mica block raw material, intercalation agent and grinding ball in the grinding tank, and use the huge impact energy and shear energy generated by the grinding ball during high-speed rotation to exfoliate the mica layer to prepare mica nanosheets, and its yield is usually greater than 80%. However, the block "crushing effect" caused by the severe impact energy between the grinding ball-grinding ball or the grinding ball-grinding tank in the ball milling exfoliation method causes the exfoliated mica nanosheets to be smaller in size and have large lattice defects. For example, patent application CN107352516A and patent application CN107352516A disclose a method for ball milling exfoliation of hexagonal boron nitride nanosheets. The hexagonal boron nitride nanosheets prepared by this method have a lateral size of less than 1 μm and introduce structural defects, which cannot meet the needs of high-performance applications. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a mica nanosheet and a preparation method and application thereof. The prepared mica nanosheet has a larger size and fewer structural defects.

[0005] The present invention provides a method for preparing mica nanosheets, comprising the following steps: S1, mica, ionic liquid and solvent are stirred and mixed, so that the ionic liquid is inserted between the mica sheets to obtain a mixed solution; The cation of the ionic liquid includes one or more of 1-alkyl imidazole, 1-alkyl-3-methyl imidazole and 1-alkyl-2,3-dimethyl imidazole cations, and the anion of the ionic liquid includes one or more of tetrafluoroborate, hexafluorophosphate, chloride and bromide; S2. The mixed solution in step S1 is subjected to ultrasonic treatment to peel off the mica sheets from each other to form mica nanosheets, and then the mica nanosheets are separated from the mixed solution through post-treatment to obtain mica nanosheets.

[0006] The invention provides a method for preparing mica nanosheets. The mica nanosheets are prepared by ultrasonic stripping technology. Compared with the existing ball milling stripping method, the invention uses ionic liquid as a small molecule intercalating agent. First, cations of the ionic liquid are exchanged with cations in mica sheets, and are combined with anions of the mica sheets by electrostatic action, and are intercalated between mica sheets. Since the ionic liquid used in the invention has a long molecular chain and a large spatial volume of anions, the anions can also be further attracted between the mica sheets. The cations and anions are inserted between the mica nanosheets together, the spacing between the mica sheets is enlarged, and the interaction force between the mica sheets is weakened, so that the mica nanosheets treated with ultrasound are easier to be stripped, and mica nanosheets with larger sizes can be prepared. Moreover, the lattice defects of the mica nanosheets are avoided, which is conducive to the large-scale preparation of large-size mica nanosheets.

[0007] In a possible implementation manner, the mass ratio of the mica to the ionic liquid in step S1 is 1:(1-50). By controlling the ratio of mica to the ionic liquid, the yield of the mica nanosheets can be controlled.

[0008] Further preferably, in step S1, the mass ratio of the mica to the ionic liquid is 1:5, 1:10, 1:20, 1:30, 1:40 or 1:50.

[0009] In a possible embodiment, the solvent in step S1 is one or more of deionized water, methanol, ethanol, ethylene glycol, glycerol, isopropanol, n-butanol and tetrahydrofuran. The use of the above solvents is conducive to uniform dispersion of the ionic liquid and allows the ionic liquid to enter the mica flakes more quickly.

[0010] In a possible implementation, the mass volume ratio of the mica to the solvent in step S1 is 1:(1-400) g / mL. By controlling the mass volume ratio of mica to the solvent, the stripping efficiency of the mica nanosheets can be controlled. When the amount of solvent is too little, the stripping efficiency is low. When the amount of solvent is too much, the stripping efficiency is not significantly improved, and the solvent is easily wasted.

[0011] Further preferably, the mass volume ratio of the mica to the solvent in step S1 is 1:2, 1:5, 1:10, 1:20, 1:25, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100 g / mL.

[0012] In a possible implementation manner, the rotation speed of the stirring and mixing in step S1 is 100-1000 rpm.

[0013] Further preferably, the rotation speed of the stirring and mixing in step S1 is 200, 300, 400, 500, 540, 600, 700, 740, 800, 900 or 940 rmp.

[0014] In a possible implementation manner, the stirring and mixing time in step S1 is 1-200 h.

[0015] By controlling the speed and time of stirring and mixing, a balance can be achieved between the intercalation efficiency of the ionic liquid and the quality of the mica nanosheets. When the speed is too low or the time is too short, the ionic liquid is inserted into the mica nanolayers at a slow speed. When the speed is too fast or the time is too long, the mica nanosheets are easily damaged.

[0016] In a possible implementation, the ultrasonic treatment mode in step S2 is a continuous ultrasonic treatment mode.

[0017] In a possible implementation manner, the ultrasonic treatment mode in step S2 is an intermittent ultrasonic treatment mode, wherein the intermittent ultrasonic treatment mode is to ultrasonicate for 1-3 hours and then stop for 0.5-1 hour.

[0018] In a possible implementation, the frequency of the ultrasonic treatment in step S2 is 1-100 kHz.

[0019] In a possible implementation, the ultrasonic treatment time in step S2 is 1-100 h.

[0020] By controlling the frequency and time of ultrasonic treatment, mica nanosheets of the desired size can be obtained. When the ultrasonic frequency is too low or the ultrasonic time is too short, it is difficult to peel off the mica nanosheets or the peeling efficiency is relatively low. When the ultrasonic frequency is too high or the ultrasonic time is too long, the mica nanosheets are easily broken and the size of the mica nanosheets becomes smaller.

[0021] In a possible implementation, the post-treatment in step S2 includes filtering, washing and drying steps.

[0022] The present invention also provides mica nanosheets prepared by the above preparation method, wherein the surface of the mica nanosheets is loaded with the ionic liquid, and the mica nanosheets have a sheet diameter of 1-5 μm and a thickness of 0.5-5 nm.

[0023] The present invention also provides the use of the mica nanosheets as barrier functional fillers for thermal conductive sheets, thermal conductive composite materials, polyesters or anti-corrosion coatings.

[0024] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.

[0025] The reagents and raw materials used in the present invention are commercially available.

[0026] The positive and progressive effects of the present invention are: (1) The method for preparing mica nanosheets provided by the present invention uses ionic liquid as a small molecule intercalant, so that the ionic liquid is intercalated in the mica sheets in the liquid phase, thereby expanding the interlayer spacing of the mica sheets, so that the mica nanosheets can be peeled off under ultrasonic treatment. Compared with the existing ball milling peeling method, the "impact crushing effect" between the grinding balls or grinding balls and grinding jars during the ball milling process is avoided, and the generation of lattice defects of the mica nanosheets during the peeling process is avoided. Moreover, the peeling can be achieved at room temperature, and the peeling process is simple, which is conducive to the high yield and large-scale preparation of large-sized mica nanosheets.

[0027] (2) The method for preparing mica nanosheets provided by the present invention also has the advantages of being recyclable, pollution-free, low cost, high yield, simple and safe process, and easy to mass-produce and scale up, and has a good industrial production foundation and broad application prospects.

[0028] (3) The mica nanosheets prepared by the preparation method of the mica nanosheets provided by the present invention are relatively large in size, with a sheet diameter of 1-5 μm and a thickness of 0.5-5 nm, and a certain amount of ionic liquid is loaded on the surface. The mica nanosheets are of high quality, few defects, low impurity content, and good dispersibility. They have good application prospects as barrier functional fillers for thermal conductive sheets, thermal conductive composite materials, polyesters or anti-corrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the SEM image of the mica nanosheets prepared in Example 1.

[0030] Figure 2 This is the TEM image of the mica nanosheets prepared in Example 1.

[0031] Figure 3 This is a comparative XRD spectrum of the mica nanosheets prepared in Example 1. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0033] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0034] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0035] Example 1

[0036] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Place 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), deionized water, and mica in a sample bottle at a mass ratio of 2:200:1, fix the sample bottle on a high-speed blender, start the blender, and stir at 540 rpm for 12 h; (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated at a frequency of 20 MHz for 4 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 54%.

[0037] Figure 1 This is a SEM picture of the mica nanosheets obtained in this example. The diameter of the mica nanosheets obtained is between 1-5 μm; Figure 2 TEM image of the mica nanosheet obtained in this example, the thickness of the mica nanosheet is 0.7 nm, and the number of layers is 1; Figure 3 This is the XRD spectrum of the mica nanosheets obtained in this example. After intercalation and stripping, the characteristic peak 2θ of mica shifts to the left and the intensity also decreases, proving that the distance between the mica nanosheets is increasing, the block structure of the mica nanosheets is destroyed, and transformed into a single-layer structure.

[0038] Example 2

[0039] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 2 g of 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 200 mL of anhydrous ethanol, and 1 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 500 rpm for 12 h. (2) Place the sample bottle in step (1) into an ultrasonic machine and ultrasonicate at a frequency of 20 MHz for 4 h. During the ultrasonication process, ultrasonicate for 2 h and stop for 0.5 h to ensure that the ultrasonic system has a suitable temperature. After the ultrasonication, filter the mica dispersion, wash it with anhydrous ethanol, and dry it in a freeze dryer to obtain mica nanosheets with a yield of 54%.

[0040] Example 3

[0041] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 4 g of 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 200 mL of deionized water, and 1 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 600 rpm for 36 h. (2) Place the sample bottle in step (1) into an ultrasonic machine and ultrasonicate at a frequency of 20 MHz for 6 h. During the ultrasonication process, ultrasonicate for 2 h and stop for 0.5 h to ensure that the ultrasonic system has a suitable temperature. After the ultrasonication, filter the mica dispersion, wash with deionized water, and dry it in a freeze dryer to obtain mica nanosheets with a yield of 60%.

[0042] Example 4

[0043] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 2 g of 1-butyl-3-methylimidazolium bromide ([BMIM]Br), 200 mL of deionized water, and 2 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 340 rpm for 24 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 40 MHz for 6 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 58%.

[0044] Example 5

[0045] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 2 g of 1-allyl-3-methylimidazolium bromide ([AMIM]Br), 250 mL of deionized water, and 1 g of mica powder, and place them in a 250 mL sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 700 rpm for 36 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 40 MHz for 6 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 61%.

[0046] Example 6

[0047] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 5 g of 1-ethyl-3-methylimidazolium bromide ([EMIM]Br), 200 mL of deionized water, and 1 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 340 rpm for 12 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 30 MHz for 4 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 53%.

[0048] Example 7

[0049] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 20 g of 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 200 mL of deionized water, and 1 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 640 rpm for 48 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 40 MHz for 6 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 63%.

[0050] Example 8

[0051] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 10 g of 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 200 mL of deionized water, and 1 g of mica powder, and put them into a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 740 rpm for 24 h. (2) Place the sample bottle in step (1) into an ultrasonic machine and perform continuous ultrasonic treatment at a frequency of 40 MHz for 6 h. After the ultrasonic treatment, filter the mica dispersion, wash it with deionized water, and dry it in a freeze dryer to obtain mica nanosheets with a yield of 60%.

[0052] Example 9

[0053] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 2 g of 1-allyl-3-methylimidazolium chloride ([AMIM]Cl), 200 mL of deionized water, and 1 g of mica powder, and place them in a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the blender, and stir at 300 rpm for 24 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 40 MHz for 6 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 53%.

[0054] Example 10

[0055] This embodiment provides a mica nanosheet, which is prepared by the following method: (1) Weigh 15 g of 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4), 200 mL of deionized water, and 1 g of mica powder, and put them into a 250 ml sample bottle. Fix the sample bottle on a high-speed blender, start the high-speed blender, and stir at 400 rpm for 48 h. (2) The sample bottle in step (1) was placed in an ultrasonic machine and ultrasonicated continuously at a frequency of 40 MHz for 7 h. After the ultrasonication, the mica dispersion was filtered, washed with deionized water, and dried in a freeze dryer to obtain mica nanosheets with a yield of 67%.

[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing mica nanosheets, characterized in that: The following steps are involved: S1, mica, ionic liquid and solvent are stirred and mixed, so that the ionic liquid is inserted between the mica sheets to obtain a mixed solution; The cation of the ionic liquid includes one or more of 1-alkyl imidazole, 1-alkyl-3-methyl imidazole and 1-alkyl-2,3-dimethyl imidazole cations, and the anion of the ionic liquid includes one or more of tetrafluoroborate, hexafluorophosphate, chloride and bromide; S2. The mixed solution in step S1 is subjected to ultrasonic treatment to peel off the mica sheets from each other to form mica nanosheets, and then the mica nanosheets are separated from the mixed solution through post-treatment to obtain mica nanosheets.

2. The method for preparing mica nanosheets according to claim 1, characterized in that: In step S1, the mass ratio of mica to the ionic liquid is 1:(1-50); And / or, the solvent in step S1 is one or more of deionized water, methanol, ethanol, ethylene glycol, glycerol, isopropanol, n-butanol and tetrahydrofuran; And / or, the mass volume ratio of the mica to the solvent in step S1 is 1:(1-400) g / mL.

3. The method for preparing mica nanosheets according to claim 2, characterized in that: In step S1, the mass ratio of mica to the ionic liquid is 1:5, 1:10, 1:20, 1:30, 1:40 or 1:50; And / or, the mass volume ratio of the mica to the solvent in step S1 is 1:2, 1:5, 1:10, 1:20, 1:25, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100 g / mL.

4. The method for preparing mica nanosheets according to claim 1, characterized in that: The stirring and mixing speed in step S1 is 100-1000 rpm; And / or, the stirring and mixing time in step S1 is 1-200 h.

5. The method for preparing mica nanosheets according to claim 4, characterized in that: The rotation speed of the stirring and mixing in step S1 is 200, 300, 400, 500, 540, 600, 700, 740, 800, 900 or 940 rmp.

6. The method for preparing mica nanosheets according to claim 1, characterized in that: The ultrasonic treatment mode in step S2 is a continuous ultrasonic treatment mode; And / or, the frequency of the ultrasonic treatment in step S2 is 1-100 kHz; And / or, the ultrasonic treatment time in step S2 is 1-100 h.

7. The method for preparing mica nanosheets according to claim 1, characterized in that: The ultrasonic treatment mode in step S2 is an intermittent ultrasonic treatment mode, wherein the intermittent ultrasonic treatment mode is to ultrasonicate for 1-3 hours and then stop for 0.5-1 hour.

8. The method for preparing mica nanosheets according to claim 1, characterized in that: The post-treatment in step S2 includes filtering, washing and drying steps.

9. A mica nanosheet, characterized in that: The mica nanosheet is prepared by the preparation method of the mica nanosheet according to any one of claims 1 to 8, the surface of the mica nanosheet is loaded with the ionic liquid, and the mica nanosheet has a sheet diameter of 1-5 μm and a thickness of 0.5-5 nm.

10. Use of the mica nanosheets according to claim 9 as barrier functional fillers for thermal conductive sheets, thermal conductive composite materials, polyesters or anti-corrosion coatings.

Citation Information

Patent Citations

  • Method for stripping white graphene by ball milling

    CN107352516A

Cited By

  • Composite conductive ink containing mica functional filler and preparation method thereof

    CN121779977A